Tibetan visions : contemporary painting from Tibet (2009)
[Dt.:] "Tibetan Visions" ist eine Online-Ausstellung bei der Werke der zeitgenössischen Malerei in Tibet sowie Fotografien von acht verschiedenen Künstlern gezeigt werden. Initiiert wurde die Ausstellung, die im Februar und März 2009 in Rom zusehen war, von der italienischen NGO Asia Onus. Hintergründe zur Ausstellung und den Initiatoren bietet ein einleitender Essay, der ebenfalls online verfügbar ist. - [Engl.:] Tibetan contemporary painting has been featured, for the first time in Italy, within the exhibition Tibetan Visions Contemporary Painting from Tibet, organized by the Italian NGO ASIA Onlus within the wider project "The Commitment of Italian NGOs in Tibet for the safeguard of Tibetan tradition and cultures", co-funded by the Italian Ministry of Foreign Affairs. The exhibition has been held in Rome at Palazzo Pamphilj from February to March 2009. The exhibition shows paintings and photographs from eight Tibetan artists.